Heritage Under Siege: The Impact of Western Culture on African Tradition - Obado Tunde Oliogu; Godfrey Obiajulu Okocha (CV Projurnal Mitra Publikasi, 2025)
The impact of Western culture on African traditions has significantly weakened the democratic norms and moral values that once united the people, causing a breakdown in social cohesion. This erosion has led to a strong resistance among Africans against any further imposition of Western ideologies, as they struggle with a lack of peace, security, unity, and love. Meanwhile, modernism asserts its superiority and dominance over African traditions and cultures, often resulting in chaos and anarchy. This paper aims to examine the ethical standards present in both African and Western cultures, advocating for values that promote hedonism, egalitarianism, peace, freedom, and justice. It analyzes Zulu Sofola's Wedlock of the Gods (1972) and Ama Ata Aidoo's The Dilemma of a Ghost (1965), which illustrate the conflict between these two cultural paradigms. These plays address traditional marriage and family dynamics, highlighting the transition from tradition to Western ideologies in the pursuit of peace and healthy relationships. The paper argues that the clash between tradition and modernity undermines humanity and should be challenged. It emphasizes the necessity of upholding individual rights and privileges to mitigate social issues such as immorality, acrimony, injustice, forced marriages, and other societal ills. Utilizing a post-colonial theoretical framework, the study is well-suited to explore the relationship between socio-cultural practices and the well-being of Africans. In conclusion, the barriers between these cultural divides should be dismantled to achieve peaceful coexistence, unity, and love.